(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT The application of digital literacy among bakery industry traders is increasingly important in the era of rapid digital transformation. However, the level of mastery and use of digital technology among small entrepreneurs is still low and unbalanced, especially in terms of strategic support from universities, industry and government. Therefore, this study was conducted to identify the role and significance of the relationship using the Triple Helix Model to understand the role of these three entities in strengthening the digital literacy of local bakery traders. The design of this study used a quantitative approach through a survey method using a questionnaire as the main instrument. Based on the Krejcie and Morgan Table, the recommended sample size for a population of 89 is 73 respondents. However, this study used 57 respondents based on the accessibility and willingness of participants to be involved, in addition to considering time and resource constraints. The questionnaire that was constructed consisted of four sections, namely demographic information (Section A), the role of the industry (Section B), the role of the university (Section C) and the role of the government (Section D). A five-point Likert scale was used to measure the perceptions of the respondents. Statistical analysis showed that there was a significant relationship between the role of industry and government (r=0.000, p<0.01), as well as a significant relationship between universities and government (r=0.304, p=0.021), and between universities and industry (r=0.419, p=0.001). This finding reflects the importance of multi-stakeholder collaboration in strengthening the development of the local bakery sector. ABSTRAK Penerapan literasi digital dalam kalangan peniaga industri bakeri semakin penting dalam era transformasi digital yang pesat. Namun, tahap penguasaan dan penggunaan teknologi digital dalam kalangan usahawan kecil masih rendah dan tidak seimbang, terutama dari segi sokongan strategik daripada pihak universiti, industri dan kerajaan. Oleh itu, kajian ini dijalankan untuk mengenalpasti peranan dan signifikasi hubungan menggunakan Model Triple Helix bagi memahami peranan ketiga-tiga entiti ini dalam memperkukuh literasi digital peniaga bakeri tempatan. Reka bentuk kajian ini menggunakan pendekatan kuantitatif melalui kaedah tinjauan menggunakan borang soal selidik sebagai instrumen utama. Berdasarkan Jadual Krejcie dan Morgan, saiz sampel yang disarankan bagi populasi seramai 89 ialah 73 responden. Namun demikian, kajian ini menggunakan seramai 57 responden berdasarkan kebolehcapaian dan kesediaan peserta untuk terlibat, di samping mengambil kira kekangan masa dan sumber. Soal selidik yang dibina terdiri daripada empat bahagian iaitu maklumat demografi (Bahagian A), peranan industri (Bahagian B), peranan universiti (Bahagian C) dan peranan kerajaan (Bahagian D). Skala Likert lima mata digunakan untuk mengukur persepsi responden. Analisis statistik menunjukkan terdapat hubungan yang signifikan antara peranan industri dan kerajaan (r=0.000, p<0.01), serta hubungan yang signifikan antara universiti dan kerajaan (r=0.304, p=0.021), dan antara universiti dan industri (r=0.419, p=0.001). Dapatan ini mencerminkan kepentingan kerjasama pelbagai pihak dalam memperkukuh pembangunan sektor bakeri tempatan.